The impact of corporate social responsibility on investment efficiency: Exploring the role of analyst forecast accuracy - Zhao, Qiujin; Sahari, Salawati; Sharon, Cheuk Choy Sheung (International Journal of Management and Sustainability, 2024)
This research investigates the direct and indirect influence of corporate social responsibility (CSR) on investment efficiency, focusing specifically on the mediating role of analyst forecast accuracy. We analyzed data from Chinese listed companies between 2010 and 2022, including a total of 21947 observations. We employed Ordinary Least Squares (OLS) regression analysis to assess the data. We used Propensity score matching (PSM) to address endogeneity, and the Boostrapt method was applied to verify the mediating effect of analyst forecast accuracy. The four-step approach results demonstrate that corporate social responsibility (CSR) positively impacts firm investment efficiency in both the full sample analysis and the analysis using propensity score matching samples. Further in-depth analysis reveals that analyst forecast accuracy plays an important mediating role in linking two factors. The Bootstrap method applied to both the total samples and PSM samples further confirms that analyst forecast accuracy serves as a partial intermediary in the relationship between the two factors. These findings not only underscore the importance of maintaining high standards of CSR practices but also provide a recommendation for financial analysts to understand better companies’ CSR initiatives and disclosure to enhance their forecasting accuracy. Evaluating firm CSR quality, as well as analyst forecast accuracy, is equally useful for those investing in potential opportunities. These factors will help reduce uncertainty in investment decision-making and improve investment efficiency.